Health Literacy Program to Reduce the Consumption of Sugary Drinks by Middle School Students in Jakarta - Wisuantari, Ni Putu Pristi; Sekarasih, Laras (Makara Human Behavior Studies in Asia, 2020)
There is a visible upward trend in the consumption of sugar-sweetened beverages across the world, and Indonesia is no exception. This study examined the effectiveness of school-based programs to increase the knowledge of junior high school students with regard to sugar-sweetened beverages in an attempt to decrease their consumption. A one week intervention using a quasi-experimental design was conducted through the adoption of the Kids SIPsmartER (Lane, et al., 2017) program. The students who received the intervention showed significantly higher nutritional knowledge of drinks with high sugar content upon completion of the program. The intervention was also successful in inducing the desired attitudes, subjective norms, and perceived behavioral control in students. The participants also evinced intentions of reducing their intake of sugar-sweetened beverages. Additionally, one week after the intervention, participating students reported that they had reduced their consumption of sugary drinks.